NAD and ADP‐ribose metabolism in mitochondria. (3rd June 2013) - Dölle, Christian; Rack, Johannes G.M.; Ziegler, Mathias
<x xml:space="preserve">Abstract</x> Mitochondrial metabolism is intimately connected to the universal coenzyme NAD. In addition to its role in redox reactions of energy transduction, NAD serves as substrate in regulatory reactions that lead to its degradation. Importantly, all types of the known NAD‐consuming signalling reactions have been reported to take place in mitochondria. These reactions include the generation of second messengers, as well as post‐translational protein modifications such as ADP‐ribosylation and protein deacetylation. Therefore, the availability and redox state of NAD emerged as important factors in the regulation of mitochondrial metabolism. Molecular mechanisms and targets of mitochondrial NAD‐dependent protein deacetylation and mono‐ADP‐ribosylation have been established, whereas poly‐ADP‐ribosylation and NAD‐derived messenger generation in the organelles await in‐depth characterization. In this review, we highlight the major NAD‐dependent reactions occurring within mitochondria and describe their metabolic and regulatory functions. We also discuss the metabolic fates of the NAD‐degradation products, nicotinamide and ADP‐ribose, and how the mitochondrial NAD pool is restored.